Frequency and Etiology of Zygomatic Complex Fractures in Oral and Maxillofacial Trauma Patients in Tertiary Care Hospital Karachi - Syeda Bisma Naseem ,Sidra Farooq, Zafar Iqbal, Faizan Ashar ,Hira Mehood, Anum Mahood (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency and etiology of zygomatic complex fractures in oral and maxillofacial trauma patients. Methods: This cross sectional study was conducted at Oral and Maxillofacial department on 116 patients presenting with oral and maxillofacial trauma. Frequency and etiology of zygomatic complex fractures in these patients were determined. Frequencies and percentages were used for categorical data while mean and SD was calculated for numerical data. Chi Square test for applied for association between categorical data. Results: Mean age of the patients was 31.52±8.19. The frequency of zygomaticomaxillary complex fractures in our study was 64 (29.3%). Most common etiology was traffic accident 16 (47.1%) followed by fall from height 11 (32.4%). Conclusion: Traffic accident was the leading etiological factor of zygomaticomaxillary complex fractures. Age groups of 20 to 30 years is the most vulnerable age group for zygomaticomaxillary complex fractures. Keywords: Etiology, Zygomaticomaxillary Complex Fractures, Oral and Maxillofacial trauma